2002
DOI: 10.1046/j.1365-2672.2002.01556.x
|View full text |Cite
|
Sign up to set email alerts
|

Combining chlorination and chloramination processes for the inhibition of biofilm formation in drinking surface water system models

Abstract: Aims: The aim of this study was to investigate the inhibition of bio®lm formation on stainless steel (SS) and galvanized mild steel (MS) in chlorine (AFC 1 ) and chlorine-monochloramine treated waters (AFC 2 M). Methods and Results: Disinfection was carried out using 2á5 mg l )1 free chlorine followed by 1á5 mg l )1 monochloramine, with non-disinfected water used as control water. Results of the standard spread plate procedure, DAPI epi¯uorescence microscopy and scanning electron microscopy revealed bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Studies showed that biofilm formation occurred even in the presence of free residual chlorine concentrations higher than 2.5 mg/1 (Momba and Binda, 2002), and also ozonation had no effect on biofilm formation on polyvinyl chloride (PVC), polyethylene (PV) and stainless steel pipe surfaces (Zacheus et al 2000). Also, biofilms induce a disinfectant demand and consequently promote disinfectant decay in distribution systems (Flemming, 2002).…”
Section: Post Uv Disinfectant Effect On Biofouling In Water Distributmentioning
confidence: 99%
“…Studies showed that biofilm formation occurred even in the presence of free residual chlorine concentrations higher than 2.5 mg/1 (Momba and Binda, 2002), and also ozonation had no effect on biofilm formation on polyvinyl chloride (PVC), polyethylene (PV) and stainless steel pipe surfaces (Zacheus et al 2000). Also, biofilms induce a disinfectant demand and consequently promote disinfectant decay in distribution systems (Flemming, 2002).…”
Section: Post Uv Disinfectant Effect On Biofouling In Water Distributmentioning
confidence: 99%
“…On the other hand, as the bulk water bacteria are living freely suspended in the water and the pipe wall biofilm bacteria are growing on a support surface, the difference may also be attributed to the varying attachment capabilities of different groups of bacteria. If the conclusion that the majority of the biomass is in the biofilm and that bulk water bacteria mainly originate from pipe wall biofilm detachment is true, then the difference could also be related to the detachment Properties of the biofilm bacteria [23]. For example, only the top layers (loose structure) are readily released into bulk water, and the inner biofilm remains attached to the pipe wall.…”
Section: Isolation Of Genomic Dna Pcr Amplification and Sequencing Omentioning
confidence: 99%
“…However, to decrease the organic content would be a very expensive process and ineffective toward bacteria in DWDS, which are able to grow in oligotrophic environments. [106][107][108] Ultra-pure water systems have been found to support the formation of biofilms, even if these systems have a lower organic content than DWDS. 79,109 Nevertheless, some European countries, notably the Netherlands, Germany, Austria and Switzerland, have taken the approach of distributing high quality DW without the use of residual chlorine.…”
Section: Pre-treatmentmentioning
confidence: 99%